Harmonic Improvement in Single-Phase Multilevel Inverter Using a Hybrid of Artificial Bee Colony (ABC) and Firefly (FFA) Algorithms - Auwal, Ibraheem; Amoo, A. L.; Mohammed, A.; Bal, Yakubu Barau; Nazif, D. M. (Darul Yasin Al Sys, 2025)
Harmonic distortion presents a significant challenge in renewable energy integration, particularly in conventional 2-level inverters. Multilevel inverters, such as the cascaded H-bridge topology, offer an effective solution by generating multiple voltage levels, thereby reducing distortion and eliminating the need for bulky filters. This study investigates harmonic reduction in a single-phase 21-level asymmetric cascaded H-bridge multilevel inverter using a novel hybrid optimization algorithm combining Artificial Bee Colony (ABC) and Firefly Algorithm (FA). The hybrid ABC-FA algorithm is designed to determine optimal switching angles for minimizing Total Harmonic Distortion (THD) while addressing the limitations of conventional heuristic methods. Modeled and simulated in MATLAB/SIMULINK, the proposed algorithm demonstrates enhanced performance in both harmonic reduction and convergence speed. Simulation results show that the hybrid ABC-FA algorithm achieves THD levels below 5%, representing a 10–20% improvement over standalone ABC or FA implementations. Additionally, the algorithm exhibits faster convergence, highlighting its effectiveness and reliability for improving power quality and facilitating efficient integration of renewable energy sources into the electrical grid.